Implementasi Good Corporate Governance (GCG) Dalam Mengukur Risiko Dan Kinerja Keuangan Bank Syariah Di Indonesia - Azizah Kurinci, Ayu Ismah; Siregar, Dewi Tamora; Rahmadhani, Nurianti; Nasution, Juliana (LPPM Universitas Labuhanbatu, 2022)
Good Corporate Governance (GCG) is one of the key factors for improving financial performance, which can help create good and responsible relationships between parts of the company (government, directors and shareholders) to improve the company's financial performance. The purpose of this research is to show the influence of good corporate governance (GCG) as represented by management ownership, institutional ownership, independent commission committees and the Sharia Board of Directors, on the measurement of financial risk and financial performance of Islamic banks in Indonesia. Overall, the results of this study indicate that the principles of good corporate governance (GCG) have no significant effect on the measurement of risk and financial performance of Islamic banks.